A philosophical critique of psychological studies of emotion: the example of jealousy. (1st September 2016) - Kristjánsson, Kristján
Abstract : The aim of this article is to provide a critical review of recent writings about jealousy in psychology, as seen from a philosophical perspective. At a more general level of inquiry, jealousy offers a useful lens through which to study generic issues concerned with the conceptual and moral nature of emotions, as well as the contributions that philosophers and social scientists can make to understanding them. Hence, considerable space is devoted to comparisons of psychological and philosophical approaches to emotion research in general. It turns out that although (Aristotle-style) arguments about the necessary conceptual features of jealousy qua specific emotion, do carry philosophical mileage, they may fail to cut ice with psychologists who tend to focus on jealousy as a broad dimension of temperament. The review reveals a disconcerting lack of cross-disciplinary work on jealousy: the sort of work that has moved the discourse on other emotions (such as gratitude) forward in recent years.